Use of Accounting Systems in Micro, Small, and Medium Commercial Sector (UMKM) in Jember District - Een yualika Ekmarinda (Indonesian Journal of Economic & Management Sciences, 2023)
According to many references, use in finance and capital is one of the main problems that hinder the development of micro, small and medium enterprises (MSMEs). The poor quality of financial records is believed to be the main cause of the low trust of banks in MSMEs. MSME owners and managers often do not have the necessary knowledge skills in applying for credit in accordance with banking standards. The purpose of this study is to understand the accounting situation of SMEs in the commercial sector of Jember Regency. According to the survey, most MSME owners and managers realize the importance of financial management through a good accounting information system for their business, and they have gone from very basic to formal accounting records